Electrically actuated 4D printed hybrid copper fiber-carbon black reinforced composites - Yahya Tavakoli; Mohsen Barmouz; Bahman Azarhoushang (Polymer Testing)
This study aims to optimize the recovery performance of electrically actuated 4D-printed customized biomedical devices by incorporating copper fibers and carbon black into various composite formulations. After extensive experimentation, six composite formulations were selected for testing under electrical actuation at two current levels: 2 A and 3 A. Results indicate that higher carbon black concentrations (0.2 %) and increased current from 2 A to 3 A significantly improved performance. The optimal composition, consisting of 20 % copper fiber and 0.2 % carbon black, achieved the highest recovery ratio of 95 % at 3 A, along with an almost 11 °C reduction in actuation temperature, highlighting its suitability for adaptive biomedical devices. While at 2 A, the same composition exhibited a recovery ratio of 76 %. Furthermore, the examined samples exhibited notable fixity ratios, ranging from 98 % to 100 %. These outcomes highlight the substantial impact of both composite material formulation and the electrical current level on optimizing recovery performance.